Laser sintering of self-healable and recyclable thermoset networks. (15th July 2022) - Cerdan, Kenneth; Brancart, Joost; De Coninck, Hellen; Van Hooreweder, Brecht; Van Assche, Guy; Van Puyvelde, Peter
Graphical abstract: Highlights: A glassy thermoset based on thermoreversible Diels-Alder crosslinks has been manufactured using selective laser sintering. Powder morphology and flow properties are suitable for selective laser sintering applications. Built parts show great healing performance, correcting partial curing and porosity generated during printing under a thermal posttreatment. Built parts are reprocessable and recyclable without altering their chemical nature. Abstract: Selective Laser Sintering (SLS) is a well-known additive manufacturing technique that builds 3D complex structures by sintering powder particles together upon laser irradiation. In the polymer field, thermoset resins are a popular choice for a plethora of applications due to their great mechanical properties and thermochemical stability. However, due to their irreversible crosslinked nature, they are hard to be processed using SLS. Herein, a covalently crosslinked polymer thermoset based on thermally reversible Diels-Alder (DA) bonds has been printed using SLS. The thermoreversible network exhibits a glassy behavior due to its high crosslinked density and glass transition temperature and was successfully milled into a suitable particle size, morphology and flow for SLS applications. At low temperatures, the DA equilibrium shifts towards the formation of the DA crosslinks, while at high temperatures the DA adducts gradually dissociate, allowing flow and reprocessability at temperatures above 131˚C. Furthermore, the printed parts exhibit healing ability when heated above their glass transition temperature, reaching a fracture stress and Young's Modulus of 25.4 MPa and 1416 MPa, respectively. Thus, the dynamic nature of the network extends the build lifetime upon damage and also brings the opportunity of recycling or reprocessing, enhancing circularity compared to classic thermosets.